Characteristics of Iranian traditional butter produced in Sarab in comparison with European and national standards - Lali Sarab, Mahmoud; Nouri, Maryam; Tarighat-Esfanjani, Ali (Progress in Nutrition, 2019)
Background/Objective: Due to the widespread use of traditional butters (TB) and the lack of reliable data and regarding insufficient supervision on their production process, this study aims to compare microbiological, physicochemical and organoleptic characteristics of Sarab’s TB with European standards (ES) and national standards (NS). Methods: In this descriptive-analytical study, fifty samples of TB were collected from the farmers of different locations of Sarab, Iran. Microbiological, physicochemical and organoleptic characteristics of butter samples were compared with ES and NS. The SPSS statistical software package version 16 and One Sample t- Test were used for comparing the mean value of parameters with standard values. Results: Our results showed that the salt content, iodine index and acidity of all samples were consistent with ES. The peroxide value, moisture and solids-non-fat content of some butter samples were higher and the fat content of 74% of them was lower than the ES values. The saponification index of 26% of samples was out of the ES range. Coliform bacteria and psychrotrophic bacteria count were higher than NS in 8% and 4% of samples, respectively. In contrast to NS, E. coli and coagulase positive staphylococcus were detected in 10% of samples. Molds and yeasts count in all samples were lower than the NS value. Score of organoleptic properties in all samples were more than 8 points. Conclusion: Despite high quality and low microbial contamination of butter samples in present study, more supervision on the production process of traditional products is recommended.